Kidney Nephron Determination - Oxburgh, Leif (Annual review of cell and developmental biology, 2018)
The nephron is a multifunctional filtration device equipped with an array of sophisticated sensors. For appropriate physiological function in the human and mouse, nephrons must be stereotypically arrayed in large numbers, and this essential structural property that defines the kidney is determined during its fetal development. This review explores the process of nephron determination in the fetal kidney, providing an overview of the foundational literature in the field as well as exploring new developments in this dynamic research area. Mechanisms that ensure that a large number of nephrons can be formed from a small initial number of progenitor cells are central to this process, and the question of how the nephron progenitor cell population balances epithelial differentiation with renewal in the progenitor state is a subject of particular interest. Key growth factor signaling pathways and transcription factor networks are discussed.